Policy Analysis of the Implementation of Merdeka Curriculum in Elementary School - Putri Lestari, Nyoman Ayu; Selpi Wahyuni, Luh Tu; Bagus Arnyana , Ida Putu; Dantes, Nyoman (Universitas Pendidikan Ganesha, 2023)
Merdeka Curriculum is a government effort to revamp primary education, facilitate more relevant, creative, and innovative situation for students. However, despite its promising concept, the Merdeka Curriculum in elementary schools still faces various challenges. One of the main issues is the lack of understanding and preparedness among schools and teachers regarding curriculum changes. This study aimed to analyze the implementation of the Merdeka Curriculum policy in elementary schools. The data analysis in this study utilizes quantitative descriptive analysis techniques. Research participants consist of teachers, principals, and staff at elementary school. The data collection technique in this study also conducted through interview, and observation is to conduct surveys by distributing questionnaires that have passed validation. The results of the research with the number of respondents were two school principals and two class teachers with a percentage of 66.68% in the very good category, then 33.32% in the good category, and no one got the adequate or poor categories for each element. The conclusion in this research is that the independent curriculum can be implemented well and needs to be improved. The significant implications of this research contribute to a deeper understanding of the policy implementation process and provide valuable insights for policymakers, school principals, teachers, and stakeholders. It recommends in further efforts to overcome the challenges faced and optimize the benefits of the Merdeka Curriculum in elementary schools.